Species differences and substrate specificity of CYP3A heteroactivation by efavirenz. (11th November 2014) - Kosugi, Yohei; Takahashi, Junzo
Abstract: 1. The purpose of this study was to clarify species differences in the heteroactivation of CYP3A substrates by efavirenz, which is known from clinical studies to activate midazolam 1′-hydroxylation, and to assess the feasibility of an animal model. 2. In monkey and human liver microsomes, efavirenz activated CYP3A-mediated midazolam 1′-hydroxylation, but had no effect in rat liver microsomes. The activating effect of efavirenz was also observed with recombinant human CYP3A4 and CYP3A5. Midazolam 4-hydroxylation, testosterone 6β-hydroxylation and the oxidation of nifedipine were not activated by efavirenz in any of the microsomes. 3. In an in vivo study using monkeys, the AUC ratio of midazolam/1′-hydroxymidazolam was reduced from 0.85 to 0.30 by efavirenz treatment, which was comparable to that obtained in clinical studies. However, the AUC changes of midazolam caused by efavirenz were smaller than those observed in clinical results, therefore the effect of efavirenz on monkeys was not completely consistent with that seen in humans. 4. In conclusion, this is the first report that efavirenz specifically activates midazolam 1′-hydroxylation only in monkey and human liver microsomes, revealing marked species differences and high substrate specificity in the heteroactivation. A further study is required to clarify whether this in vitro r esult reflects the in vivo situation.